2018
DOI: 10.1002/cvj.12089
|View full text |Cite
|
Sign up to set email alerts
|

Everything Is More Critical: A Qualitative Study of the Experiences of Young Breast Cancer Survivors

Abstract: Receiving a breast cancer diagnosis at a young age has the potential to affect survivors' worldview and raise existential concerns. This qualitative study of 13 women diagnosed with breast cancer before the age of 40 examined how they made meaning of the impact of their cancer experience. Implementing the consensual qualitative research methodology, the authors found themes related to challenges; coping strategies; reappraisal of self, relationships with others, and life roles; and changes in views and behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 47 publications
3
19
0
Order By: Relevance
“…This study is the first, to our knowledge, that has specifically explored the experiences of women who have made a positive career change as a result of their breast cancer. Some of the findings resonate with previous literature which highlights the positive growth and renewed sense of self, that cancer or chronic illness can bring (for example, Beatty, 2012;Raque-Bogdan et al, 2018), but this study adds to the existing literature showing how this personal growth can manifest itself in a career change. Specifically, the findings show how the women's experiences of cancer led to a sharply focused sense of self which gave them clarity about their new career goals, and a renewed sense of agency which enabled them to put their career plans into action.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This study is the first, to our knowledge, that has specifically explored the experiences of women who have made a positive career change as a result of their breast cancer. Some of the findings resonate with previous literature which highlights the positive growth and renewed sense of self, that cancer or chronic illness can bring (for example, Beatty, 2012;Raque-Bogdan et al, 2018), but this study adds to the existing literature showing how this personal growth can manifest itself in a career change. Specifically, the findings show how the women's experiences of cancer led to a sharply focused sense of self which gave them clarity about their new career goals, and a renewed sense of agency which enabled them to put their career plans into action.…”
Section: Discussionsupporting
confidence: 84%
“…The existing literature on cancer survivors suggests that these career development models may have some relevance to the present study. Research has shown that survivors' experiences of cancer can lead to boundaries being shed as survivors wonder why it has taken the trauma of their cancer diagnosis to engage with their lifelong goals (Raque-Bogdan et al, 2015), and can lead to more meaningful life choices (Raque-Bogdan et al, 2018).…”
Section: Theoretical Underpinningmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 28 studies , five aimed to explore both positive and negative experiences [28,32,41,49,54] and 15 were focused only on positive experiences, either framed in terms of PTG or positive constructs such as meaning-making [30, 33-38, 43, 45-48, 51, 53, 55]. In six studies, the stated aim was broader (e.g., the original research question had a focus on areas such as adjustment or lasting life changes after cancer) but results were reported with a focus on the positive changes found [29,31,39,42,44,52]. Two studies had very specific aims -exploring differences between people with cancer and their spouses in terms of growth [40] and an examination of growth in relation to other constructs, such as lifestyle changes [50].…”
Section: Study Aimsmentioning
confidence: 99%
“…Furthermore, the majority of previous studies of meaning making among breast cancer survivors are quantitative studies based on questionnaire data (e.g., Sears et al, 2003;Majerníková and Obročníková, 2017;Krok and Telka, 2018). Although studies taking the interpretative phenomenological perspective on meaning making in the population of breast cancer survivors exist, most include data from both young and older survivors (Gall and Cornblat, 2002;Collie et al, 2006;Fallah et al, 2012;Raque-Bogdan et al, 2018;Rashidi et al, 2020). Keeping in mind the increased rate of older cancer survivors in the future, there is a lack of qualitative studies focusing on meaning making in the group of older breast cancer survivors.…”
Section: Incongruence and Meaning-based Copingmentioning
confidence: 99%